Bank systems management : the project management guide to planning and implementing system installations, conversions, and mergers - Belasco, Kent S. (Chicago, Ill. : Probus Pub. Co., 1994)
The book helps you answer the perplexing questions involved in systems conversions, installations and ongoing operations. It includes detailed discussion on the critical issues in systems management including project planning, cost/benefit analysis, vendor and staffing issues, systems implementation and operational analysis.
Includes bibliographical references and index.
rua 09/11/16
Loans
Keywords: Banks and banking; Bank management; Project management